Contribution of Abu Yusuf's Thoughts in The Book Al-Kharaj Towards Sharia Taxes In KPBU: Analysis of DSN-MUI Fatwa No. 156 of 2023 - Setiawan Bin Lahuri; Briandika Yudha Wardhana (Golden Ratio of Law and Social Policy Review, 2026)
Income inequality and high poverty rates are significant problems for developing and even developed countries in the world. Thus, the distribution of income to improve welfare and reduce poverty is urgently needed. Many instruments in Indonesia provide a distribution process, one of which is with taxes. However, the problem is that the Indonesian tax system often contains errors or fails to comply with Sharia principles. This research is a quantitative, descriptive study using a library research method and a qualitative content analysis approach. This study uses secondary data as its primary data. The researcher will examine and review previous literature, including journals, articles, books, and websites, that provide information on the tax distribution process. So that the collection of taxes from the community is inappropriate and results in increased income inequality. Given this phenomenon, this research is essential for understanding the appropriate Sharia tax system as outlined in the book Al-Kharaj, as seen in the DSN-MUI fatwa no. 156 of 2023 is needed, as well as providing solutions to the obstacles faced. This research has the following objectives: to understand, analyze, and determine the relevance of implementing Sharia taxes in Indonesia, as outlined in Fatwa No. 156 of 2023, to the concept of taxes put forward by Abu Yusuf in the book Al-Kharaj.